Development and Validation of an Educational Booklet to Improve Occupational Performance of the Primary Caregivers of Individuals With Multiple Sclerosis - Mohammad Taghi Mohseni Takalu; Seyed Ali Hosseini; Hamid Reza Khankeh; Ebrahim Pishyareh; Enayatollah Bakhshi (University of Social Welfare and Rehabilitation Sciences, 2020)
Objective: Caring for individuals with multiple sclerosis (MS) can affect their caregivers' occupational performance in various areas such as work, rest/sleep, and social participation. Part of the rehabilitation process is educating caregivers. Primary caregivers need knowledge and information to deliver their caring role. Although face-to-face learning is useful, it can have some limitations. For example, a caregiver should refer to a specific center to receive information and interventions, which is often time-consuming and may trouble them to perform other roles, including their occupational roles. Written health education is used for complementing or strengthening verbal education and maximizing its effectiveness. These materials play an essential role in increasing knowledge, self-management, and commitment to treatment. When health professionals and health services are not available to caregivers, written health education materials can partially answer their questions and needs. It can also help reduce the costs of health care for caregivers. The present study aims to develop and validate the appearance and content of an educational booklet to improve the occupational performance of primary caregivers of individuals with MS (PCIMS). Materials & Methods: This is a methodological study conducted. 1. preparing the content based on grounded theory study of PCIMS and their challenges, and then preparing an initial draft, 2. examining the face validity and content validity of the initial draft according to the opinions of 22 experts in MS, and 3. examining the face validity and content validity of the initial draft according to views of 22 PCIMS. An item-level content validity index (I-CVI) value of ≥0.78 and a scale-level content validity index/average (S-CVI/Ave) value of ≥0.9 were considered as the criteria for having acceptable validity in the second and third phases. The binomial test was also used to test the statistical reliability of the I-CVIs at a significance level of 0.05 and the expected proportion of agreement (test proportion) of 0.8. Results: The minimum I-CVI and S-CVI/Ave values for the items of a scale designed to assess the face validity and content validity of the booklet were respectively reported 0.9 and 0.97, according to the panel of experts. Also, the minimum observed proportion of agreement for items under the binomial test was obtained 0.9, which was higher than the expected proportion of agreement (0.8). I-CVIs values, S-CVI/Ave value and the observed proportion of agreement between PCIMS were equal to 1. For participating experts and PCIMS, the booklet had appropriate validity, and their comments on the appearance and content of the booklet were applied to the final version of the booklet. Conclusion: The developed educational booklet has acceptable face validity and content validity, and specialists can use it for the rehabilitation intervention of PCIMS. Further studies are recommended to investigate the effectiveness of this booklet on improving the quality of life of PCIMS.